Investigation of surface adhesion produced by high-speed flame spraying; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 3 - Klimenov V. A. Vasily Aleksandrovich; Kovalevskaya Zh. G. Zhanna Gennadievna; Zaitsev K. V. Konstantin Viktorovich; Tolmachev А. I. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа